Salvia divinorum: from recreational hallucinogenic use to analgesic and anti-inflammatory action - Coffeen U; Pellicer F (Journal of Pain Research, 2019)
Ulises Coffeen, Francisco Pellicer Research in Neurosciences, Instituto Nacional de Psiquiatría Ramón de la Fuente Muñiz, Mexico City, México Abstract: Salvia divinorum is a herbal plant native to the southwest region of Mexico. Traditional preparations of this plant have been used in illness treatments that converge with inflammatory conditions and pain. Currently, S. divinorum extracts have become popular in several countries as a recreational drug due to its hallucinogenic effects. Its main active component is a diterpene named salvinorin A (SA), a potent naturally occurring hallucinogen with a great affinity to the κ opioid receptors and with allosteric modulation of cannabinoid type 1 receptors. Recent biochemical research has revealed the mechanism of action of the anti-inflammatory and analgesic effect of SA at the cellular and molecular level. Nevertheless, because of their short-lasting and hallucinogenic effect, the research has focused on discovering a new analogue of SA that is able to induce analgesia and reduce inflammation with a long-lasting effect but without the hallucinatory component. In this review, we explore the role of S. divinorum, SA and its analogues. We focus mainly on their analgesic and anti-inflammatory roles but also mention their psychoactive properties. Keywords: Salvia divinorum, salvinorin A, pain, inflammation, psychoactivity